Literary Works for Early-Age Students: Knitting Social Class, Literacy, & Culture in Parenting Blockades - Setiawan, Rahmat; Agustina, Eliasanti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This research discusses the challenges of teachers in implementing learning by using literature for early childhood. The concepts used in this research are literary works, parenting, and challenges. The approach in this research is ethno-narrative. The data used in this study are snippets of statements obtained from interview transcripts. The type of interview conducted is a non-structured interview that explores the teachers' narrative experiences. 2 teachers in early age school are used as resource persons in this study. The analysis technique uses narrative. The results of the analysis explain that: 1) The parents are working class, meaning that their social class is lower middle class; 2) lower middle class indicates a lack of literacy related to parenting, 3) lack of literacy creates a culture which blockades the learning for children using literary works.